COVID-19 Management in Iran as One of the Most Affected Countries in the World: Advantages and Weaknesses - Rassouli, Maryam; Ashrafizadeh, Hadis; Shirinabadi Farahani, Azam; Akbari, Mohammad Esmaeil (Frontiers in Public Health, 2020)
now among hot topics due to its sensitivity. How a crisis is managed in each country is influenced by several factors, and various strategies are applied in accordance with these factors in order to manage the crisis. Due to the rapid spread and increasing trend of the crisis and the fact that almost more than half of the countries are engaged in this pandemic, it is impossible to apply trial-and-error based strategies. One of the best strategies is to use the experiences of other countries in dealing with COVID-19. This report explores the advantages and weaknesses of the Islamic Republic of Iran in the management of this crisis in regard with political economic and cultural issues, health service coverage and the transparency of information that can be used as a model for other countries around the world.